2011
DOI: 10.1093/occmed/kqr071
|View full text |Cite
|
Sign up to set email alerts
|

The health and well-being of remote and mobile workers

Abstract: There is little research currently available on the general health of RMWs and future research should examine this further and focus on general health and access to support services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 15 publications
1
28
0
15
Order By: Relevance
“…The authors found that musculoskeletal symptoms among mobile workers improve with proper ergonomic interventions (Crawford et al, 2011). Strong evidence suggested that neck, shoulders, and low back were the most common areas of occupational injury (Crawford et al, 2011), validating the findings of the Hauke study. Loeppke et al (2013) found that "by utilizing the principles of safe design, musculoskeletal injuries on the job can be decreased when preventive interventions are correctly implemented" (p. 503).…”
Section: Stress At Worksupporting
confidence: 52%
“…The authors found that musculoskeletal symptoms among mobile workers improve with proper ergonomic interventions (Crawford et al, 2011). Strong evidence suggested that neck, shoulders, and low back were the most common areas of occupational injury (Crawford et al, 2011), validating the findings of the Hauke study. Loeppke et al (2013) found that "by utilizing the principles of safe design, musculoskeletal injuries on the job can be decreased when preventive interventions are correctly implemented" (p. 503).…”
Section: Stress At Worksupporting
confidence: 52%
“…[2,15,27,28] These are summarised in Table 2. Teleworkers spend less time travelling, commuting and away from home.…”
Section: Pros and Cons Of Teleworkmentioning
confidence: 99%
“…The overall effect on health is neither well known nor consensual. [27,30] Most empirical work reports positive and negative effects but there has been little analysis of the trade-offs associated with telework and its net benefits or net costs.…”
Section: Health Issues Associated With Teleworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The occupational health literature highlights how mobile workers, especially those spending large amounts of time driving, experience increased risk of musculoskeletal symptoms and lower levels of mental health due to long working days, high work demands, and lowered interaction with colleagues [19,20]. Mulki et al [55] identified that feelings of isolation in such workers could occur due to multivariate issues including a lack of personal contact with colleagues, losing a sense of camaraderie, and feelings of being 'left out'.…”
Section: Mobile and Lone Working And Occupational Healthmentioning
confidence: 99%